Moral Value Of Dikir Barat : Case Study Of Cikgu Naim Lyric. - Anis Suhaila Mohd Rizal (2021)
This study focuses on the moral values found in the lyrics of Dikir Barat song by Cikgu Naim, a Kelantanese dikir barat performer whom has produced many songs that denoting the moral values and current issues that society encountered. Based on this study, various types of moral values have been identified. This study can prove that this dikir barat song is not only an entertaining performance of the Kelantanese, but also has significant messages to convey in both directly and indrectly as the motivational support to community. Bases on the findings, researcher suggests that these Cikgu Naim's dikir barat songs can be introduced and functioned as a traditional media to instil the morality, to the community, especially the younger generation. From this, the value of Dikir Barat songs will be presented , emphasized, and carried on for the future generation.